Pendampingan Guru dalam Pencegahan Sindrom Metabolik di SMA N 1 Bergas, Kabupaten Semarang - Afiatna, Puji; Sugeng Maryanto; Umi Setyoningrum; Untari; Anisa Puspitasari (UNIVERSITAS NGUDI WALUYO, 2025)
Metabolic syndrome is a condition that can lead to the development of cardiovascular disease (CVD), coronary heart disease (CHD), and type 2 diabetes mellitus (T2DM). These diseases are frequently referred to as